Polymer Rheology - Luis Rivera-Armenta, Jose; Adriana Salazar Cruz, Beatriz (IntechOpen, 2018)
Rheology is the science that studies the behavior of the flow of matter in a liquid state or soft solids under the application of stress or deformation to obtain a response to an applied force. In polymers, rheology is an important tool to understand behavior under processing conditions and to design equipment. Another application for rheology in the polymer field is to understand structure-property relationships by means of molecular weight, molecular weight distribution, stereochemistry, morphology, melt degradation, and performance under processing. This book covers the essential criteria for selecting the best test types for various applications and new developments, for accurately interpreting results, and for determining other areas where rheology and rheological phenomena may be useful in your work.